Professional C++ - Gregoire, Marc (John Wiley & Sons, Inc., 2024)
Expand your C++ knowledge quickly and efficiently with this advanced resource In the newly revised sixth edition of Professional C++, veteran software engineer and developer Marc Gregoire delivers yet another volume that raises the bar for advanced programming manuals. Covering almost all features of the new C++ standard codenamed C++23, the book offers case studies with working code that's been tested on Windows and Linux. As the leading resource for dedicated and knowledgeable professionals seeking to advance their C++ skills, this book provides resources that help readers: Master new features of the latest standard, C++23 Maximize C++ capabilities with effective design solutions Discover little-known elements and learn about pitfalls and what practices to avoid Grasp testing and debugging best practices Learn about tips and tricks for efficiency and performance C++ is a complex language. Professional C++, 6th Edition , allows dedicated practitioners to remain current and abreast of the latest developments and advances.
Description based on online resource; title from digital title page (viewed on January 17, 2024)
Keywords: C++ (Computer program language); C++ (Langage de programmation)